Withdrawal of Life-Sustaining Therapy after Cardiac Arrest - Cronberg, Tobias; Kuiper, Michael (Seminars in Neurology, 2017)
An increasing number of patients are successfully resuscitated from cardiac arrest (CA) and subsequently treated in an intensive care unit due to unconsciousness. Approximately half of these patients will die during the first weeks postarrest, typically after a determination of a poor neurologic prognosis and a decision to withdraw life-sustaining therapy (WLST). These decisions are guided by universal ethical principles. Neurologic prognostication, WLST, and functional outcome after CA are closely correlated, but routines vary between and within countries. Recent studies indicate that premature decisions to withdraw care may be common. This topical review will focus on the decision of WLST for patients remaining unconscious after CA, the guiding ethical principles, and the interaction with neurologic prognostication and outcome.
Keywords: cardiac arrest; life-support care; mortality; advance directive